The economic and monetary union: Past, present and future - Marek Dabrowski (Center for Social and Economic Research (CASE), 2019)
Twenty years of euro history confirms the euro's stability and position as the second global currency. It also enjoys the support of majority of the euro area population and is seen as a good thing for the European Union. The European Central Bank has been successful in keeping inflation at a low level. However, the European debt and financial crisis in the 2010s created a need for deep institutional reform and this task remains unfinished.
Keywords: E58; E62; E63; F33; F45; H62; H63; 330; European Union; Economic and Monetary Union; common currency area; monetary policy; fiscal policy